2022
DOI: 10.1155/2022/2586307
|View full text |Cite|
|
Sign up to set email alerts
|

Value Proposition for Enabling Construction Project Innovation by Applying Building Information Modeling

Abstract: Building information modeling (BIM) is evolving as a digital infrastructure model for innovation in the construction field. The innovation-enabling potential of BIM has been highly neglected in the literature. This study explores the innovative potential of BIM, specifically its value in enabling construction innovation (CI). Through reflective research and a literature review, the relationship between BIM and CI is redefined, BIM-CI’s value spectrum and underlying mechanisms are mapped and their required reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Known as Construction 4.0, the current AEC landscape is witnessing a convergence of digital innovations, shaping smart and sustainable construction practices (Sawhney et al, 2020;Forcael et al, 2020;Perrier et al, 2020). Additionally, the shift towards Construction 5.0 and Society 5.0 highlights the importance of societal well-being, advocating for a holistic approach that combines technological advancements with human-centric development (Yitmen et al, 2023;Marinelli, 2023;Chen et al, 2022;Musarat et al, 2023;Liu et al, 2022). In the pursuit of smart and sustainable construction, this study highlights the crucial role of data-driven technologies, particularly IoT, computing models, and big data solutions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Known as Construction 4.0, the current AEC landscape is witnessing a convergence of digital innovations, shaping smart and sustainable construction practices (Sawhney et al, 2020;Forcael et al, 2020;Perrier et al, 2020). Additionally, the shift towards Construction 5.0 and Society 5.0 highlights the importance of societal well-being, advocating for a holistic approach that combines technological advancements with human-centric development (Yitmen et al, 2023;Marinelli, 2023;Chen et al, 2022;Musarat et al, 2023;Liu et al, 2022). In the pursuit of smart and sustainable construction, this study highlights the crucial role of data-driven technologies, particularly IoT, computing models, and big data solutions.…”
Section: Introductionmentioning
confidence: 99%
“…This data-driven approach ensures that buildings are energy-efficient, water-saving, and provide a healthy environment for occupants. Furthermore, Construction 5.0 promotes the use of renewable energy sources such as solar power and wind energy in construction projects (Chen et al, 2022;Liu et al, 2022). Smart grids and energy management systems optimize the utilization of renewable energy, ensuring a sustainable power supply for construction sites and completed buildings alike.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are still a few cases of BIM being used in construction projects in China, but research on BIM has already started. Some universities have set up BIM research groups to research BIM theory, BIM software, and BIM applications [31]. e research and development of BIM and the use of BIM technology to build an information platform to facilitate the efficient implementation of the whole process of construction project cost management will be a key focus of future research and development in the field of construction project costing in China.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%